Three-dimensional computational analysis of flow over twisted hydrofoils - Oksuz, Sinem; Celik, Fahri; Bayraktar, Seyfettin (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
The hydrofoils are frequently employed in many different industrial applications, including submarines, rudders, ship motion controls, and marine propellers. The flow over hydrofoils has been the subject of various research in the past. The present study reports the effects of varying twist applied symmetrically along the span and the section thickness on the hydrodynamic performance parameters of non-cavitating three-dimensional hydrofoils for a relatively wide range of angles of attack. Twisted, half-twisted and untwisted hydrofoils with NACA0009 and NACA0015 sections are investigated numerically by incompressible non-cavitation model of Reynolds -Averaged Navier-Stokes (RANS) equations with the shear stress transport (SST) k-omega turbulence model. The impact of twisting, section thickness and freestream velocity are studied in terms of the distributions of lift, drag, and pressure coefficients for various angles of attacks -2 degrees <8 degrees following a series of successful validation processes. Twisted hydrofoils are evaluated for the implications of the altered incoming flow velocity on the hydrofoil performance. The Delft Twist-11 hydrofoil, which has been used as a benchmark geometry in the literature, are employed for validation investigations. The purpose of the study is to identify which of the hy-drofoils under investigation (twisted, half-twisted, untwisted) has a higher lift force and efficiency, and whose application would be more suitable for a particular angle of attack. In particular, the twisted NACA0009 provides the highest lift and the highest efficiency in the range of -2 degrees <2 degrees compared to half-twisted and untwisted cases. From AOA = 2 degrees -5 degrees, half-twisted NACA0009 provides the maximum efficiency; at later angles, untwisted NACA0009 performs better. Additionally, the lift force is not much affected by the rise in Reynolds number of flows around twisted hydrofoils, while the drag coefficient significantly decreases.
Keywords: Twisted wings; Delft Twist-11; Hydrodynamics; Computational fluid dynamics; Turbulence; LARGE-EDDY SIMULATION; CAVITATING TURBULENT-FLOW; RESOLUTION; VORTICITY; RUDDER; Engineering; Oceanography